Struktur Caring Pada Mahasiswa Keperawatan (Caring Structure In Nursing Students) - Maria Manungkalit; Made Indra Ayu Astarini; Ida Ayu Febiana Ida Ayu Febiana Ida Ayu Febiana (JURNAL NERS LENTERA, 2021)
The caring attitude of students tends to be lacking so that it can have an impact on the quality of nursing care services to patients during clinical practice. The purpose of this study was to describe the Strukturons of caring for nursing students. Methods This type of research was analytic observational with a cross sectional design. The research population was all students of the nursing faculty at a private campus in Surabaya as many as 122 people, where the sampling technique used total sampling. The research instrument used a caring questionnaire that has been tested for validity and reliability. Results The majority of respondents have a good caring attitude as many as 84 respondents (69%). The results of the analysis with ordinal regression obtained that the Strukturon of knowing in caring has the largest Nagelkerke coefficient, which is 0.528, which means that knowing has a large influence of 52.8% on students' caring attitudes. Discussion The caring attitude of students on the Strukturon of knowing has the greatest value because at this stage it is often done by students to obtain patient data as nursing assessment data that is useful for determining patient problems. Conclusion Five Strukturons of caring have a great influence on the caring attitude of students.